Fostering Scientific Literacy using RADEC Learning Model in Junior High School - Tillah, Nurmazia Firahma; Subekti, Hasan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Scientific literacy is the ability of individuals to engage with science-related issues and scientific ideas as reflective citizens. However, many students struggle with low scientific literacy skills, which hampers their ability to understand and engage with scientific concepts effectively. This study aims to describe the implementation of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model on the scientific literacy of junior high school students. This type of research is experimental design. The research design used is descriptive with a one-group pretest-posttest design. The subjects of this study were 34 students of class VII-G at SMP Negeri 54 Surabaya during the even semester of the academic year 2023/2024. Data collection techniques involved observation, tests, and questionnaires. Research instruments included learning implementation observation sheets and scientific literacy tests. Test results were analyzed using N-Gain (Normalized Gain) and paired sample t-test. The study's findings revealed that the implementation of the RADEC learning model was executed very well, as evidenced by an average implementation score of 98.6%, which was categorized as very good. Second, students' scientific literacy skills showed improvement after the RADEC learning model was implemented, as seen from the N-gain analysis, with a score of 0.60, categorized as moderate. The paired sample t-test analysis indicated a significant difference in improving students' scientific literacy skills before and after the learning process with the RADEC learning model.